THE MODELLING PROCESS AS AN INSTRUCTIONAL STRATEGY IN LANGUAGE TEACHING PROCESS: Strategies in Language Teaching Process - Besjana Rexhepi (Pendas Mahakam : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2021)
Modelling has to be considered as a new form of learning or as a facilitation of learning units from the students' side, but also for teachers too in the form of teaching units. From modelling, teachers demonstrate units or different teaching tasks to their students so they can understand them more easily. Modelling it is become like a bridge between students and teachers too, because from it all the lessons become more clear. Through modelling, students are actively involved in the learning process and interactive methods enable students to take initiatives. They combine initiatives, talk on behalf of the group in which they carry out their work, create new communication relationships with each other. And through modelling, the quality of classroom learning increases. Modelling can be useful to provide pupils with a couple of ‘pointer’ questions in order to focus the discussion and to link the discussion to pupils’ prior knowledge. Writing down the main points to emerge from the discussion on the board or a flipchart help to focus pupils and also emphasize the fact that the discussion is a learning activity and not a just a way of filling time. Learning is always an active process. The learner actively constructs her/his learning from the various inputs s/he receives. This implies that the learner needs to be active to learn effectively. Learning is about helping pupils construct their own meaning, not about ‘getting the right answer’, as pupils can be trained to get the right answer without actually understanding the concept. Therefore part of this Seminar’s paper are types of language’s teaching modelling, advantages and disadvantages of this strategy then some of examples described in the classroom education process. Towards that in this paper we tried to give some definitions given from foreign and native authors, who have talked about the modelling process into language teaching. Key words; Challenge, Creativity, Modelling, Method, Strategy.